Honorable Bandit A Walk across Corsica - Bouldrey, Brian (The University of Wisconsin Press, 2007)
Brian Bouldrey traveled to the island of Corsica, with its wine-dark Mediterranean waters, powdered-sugar beach sand, and a cuisine and wines fit for the rich. And then he walked away from all of them. Bouldrey strapped on a backpack and walked across Napoleon's native land with the same spirit many choose to dance or drink: to celebrate, to mourn, to think, to avoid thinking, to recall, to ignore, to escape, and to arrive.